Discovery Learning Versus Traditional Learning: How Effective Discovery Learning Can Improve Mathematical Creative Thinking Skills - Mustafa, Ade Nandang; Lasmaya, Deni (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2020)
The present study aims to understand the effectiveness of discovery learning in increasing mathematical creative skills in comparison to traditional learning methods. This study uses a non-equivalent control group research design. The variables in this study include independent variables, namely Discovery Learning and Traditional Learning, and the dependent variable is the mathematical creative thinking skill, while the control variable is a group of students' initial ability categories (top, middle, and bottom). The research sample consisted of two groups of 39 grade 7 students selected using a random assignment technique from one junior high school in Lembang, Indonesia. The data were obtained through mathematical creative thinking skills tests. Overall, the improvement in mathematical creative thinking skills of students who received Discovery Learning is better than students who received traditional learning. In the top and middle categories, the improvement of mathematical creative thinking skills of students who received Discovery Learning is better than students who received traditional learning. While the groups are in the bottom category, the mathematical creative thinking skills of students who get discovery learning is no better than students who get traditional learning.